Japanese theatre - Bowers, Faubion (Hermitage House, 1952)
The reader will find no fuller and more informed account of the complexities of Japanese theatre history and of the cultural matrices from which Japan's various theatre forms grew, than in this admirable scholarly work. - The book represents the summation of a lifetime's work by a meticulous teacher and scholar whose fascination with his subject now allows him to share his knowledge, and his enthusiasms, with a larger audience.